Implementasi Program Keluarga Harapan (PKH) dalam Meningkatkan Kualitas Hidup RTSM di Kecamatan Kediri Kabupaten Tabanan - Darmayanthi, Ni Putu Ayu Mia; Yasintha, Putu Nomy; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2019)
ABSTRACT Program Keluarga Harapan (PKH) is a social protection program that provides cash assistance to Rumah Tangga Sangat Miskin (RTSM) that aim to improve the quality of life of poor families bye providing the goverments the fields of education, health and social welfare as a form of social protection based on the Decree of the Minister of Social Affairs of the Republic of Indonesia Number: 42 / HUK / 2007. The results of this study indicate that all implementation indicators have been included in the implementation of Program Keluarga Harapan and can improve the quality of life of RTSM as evidenced by the PKH graduation but in implementation there are still obstacles, namely the PKH assistants or assistants who are less than the PKH recipients. This study resulted in recommendations for improving the implementation of family programs in the hope of improving the quality of life in Kediri District, Tabanan Regency. Keywords: Implementation, Program Keluarga Harapan, RTSM Quality of Life